Concentration-dependent apparent partition coefficients of ionic liquids possessing ethyl-and bi-sulphate anions - Jain, Preeti; Kumar, Anil (Physical Chemistry Chemical Physics, 2016)
This study deals with the concentration dependent apparent partition coefficients log P of the ethyl and bisulfate-based ionic liquids. It is observed that the bisulfate-based ionic liquids show different behaviour with respect to concentration as compared to ethyl sulphate-based ionic liquids. It is significant and useful analysis for the further implementation of alkyl sulfate based ionic liquids as solvents in extraction processes. The log P values of the ethyl sulphate-based ionic liquids were noted to vary linearly with the concentration of the ionic liquid, whereas a flip-flop trend with the concentration for the log P values of the bisulphate-based ionic liquids was observed due to the difference in hydrogen bond accepting basicity and possibility of aggregate formation of these anions. The pi-pi interactions between the imidazolium and pyridinium rings were seen to affect the log P values. The alkyl chain length of anions was also observed to influence the log P values. The hydrophobicity of ionic liquid changes with the alkyl chain in the anion in the order; [HSO4](-) < [EtSO4](-) < [BuSO4](-).